(untitled) (Nigerian Journal of Technology, 2015)
The effect of sugar cane juice, (SCJ) on slump values, setting time and compressive strength of concrete cubes was investigated. A total of 32 concrete cubes of size 150x150x150mm with a mix ratio of 1:2:4 were cast with different percentages of unfermented sugar cane juice replacing some proportion of water in the concrete mix. Water/Sugar Cane Juice/cement ratio was held constant at 0.45. The concrete cubes were prepared by replacing water with SCJ in the following proportions 0, 25, 50 and 100%. The cubes were cured, tested and the physical properties of interest in this study were determined. The slump values of the concrete decreased from 40mm at 100: 0 (water:SCJ) to 18mm at 50:50 (water:SCJ) and to 0mm (collapse) at (0:100) (water :SCJ). The final setting time of concrete increased with increase in proportion of SCJ. The highest final setting time of 42 hours (considered excessive), occurred at 75:25 (water:SCJ) proportion. The compressive strength of the (water:SCJ) concrete decreased as the percentage of SCJ increased up to 25% SCJ. Thereafter, an increase in compressive strength was noticed up till 100% SCJ, with a maximum strength of 13.08N/mm2 occurring at 100% SCJ at 28 days. The early strength reduction is due to quick-setting of the concrete, at 25% SCJ, retardation commences and the strength of concrete increases. The study has been carried out at 0, 25, 50 and 100% replacement by weight of potable water with SCJ. A comparative study has been done between concrete made with potable water and those made with water/sugar cane juice. http://dx.doi.org/10.4314/njt.v34i2.6